Exponential of Sum/Real Numbers/Proof 1
Jump to navigation
Jump to search
Theorem
Let $x, y \in \R$ be real numbers.
Let $\exp x$ be the exponential of $x$.
Then:
- $\map \exp {x + y} = \paren {\exp x} \paren {\exp y}$
Proof
This proof assumes the definition of $\exp$ as:
- $\exp x = y \iff \ln y = x$
where:
- $\ln y = \ds \int_1^y \dfrac 1 t \rd t$
Let $X = \exp x$ and $Y = \exp y$.
From Sum of Logarithms, we have:
- $\ln X Y = \ln X + \ln Y = x + y$
From the Exponential of Natural Logarithm:
- $\map \exp {\ln x} = x$
Thus:
- $\map \exp {x + y} = \map \exp {\ln X Y} = X Y = \paren {\exp x} \paren {\exp y}$
$\blacksquare$
Alternatively, this may be proved directly by investigating:
- $\map D {\map \exp {x + y} / \exp x}$
Sources
- 1977: K.G. Binmore: Mathematical Analysis: A Straightforward Approach ... (previous) ... (next): $\S 14.5 \ (1) \ \text {(i)}$